Peran Orang Tua di Era Digital - H. M. Taufik Amrillah; Amanah Rahmaningtyas; Meri Hartati; Gladis Agustin (Insititut Agama Islam Negeri (IAIN) Curup, 2020)
This article discusses the role of parents in the digital age. The digital Era is characterized by the presence of technology, where there is an increase in the speed and flow of knowledge turnover in the economy and community life. Parents who are part of the information society cannot avoid that children in the digital age never escape from objects related to technology. The increase of digital technology in children's developmental life invaded many development phases that the child should achieve. Technology makes their lives faster (instant) and more efficient. Entertainment technologies such as television, internet, video games, iPod, iPad, and others have grown so rapidly that it makes a family hardly aware of the significant impact and lifestyle changes in their families. The education undertaken anciently differed from today's education. As new knowledge and technologies and cultural shifts are caused by thought patterns that are influenced by information obtained in a very easy way. It is demanding that parents always update/upgrade their knowledge in order to give direction to their children in a wise way. Parents need to accompany to avoid unwanted things so that the concern of parents and educators of early childhood in the digital age is the importance of the introduction of religious values, local wisdom, so as to fortify the child from global influences.